Variable morphology of Mandibular First Molar roots and canals: A Literature Review - Buzaribah, Khadeejah; Salih, Randa; Areibi, Aisha (Libyan Journal of Dentistry, 2018)
A precise knowledge of the anatomical characteristics of the various types of human teeth and their possible morphological variations is considered one of the fundamental elements for a successful treatment in various subjects of dentistry especially in endodontic. Studies revealed that improper exploration of all canals of an endodontically treated tooth for subsequent disinfection and obturation may result in failure of the endodontic therapy. Over the years, there have been numerous researches and studies that described the morphology of all teeth including mandibular first molar. The root canals of permanent mandibular first molar in human dentitions exhibit extensive anatomical variations and abnormalities in its number and configuration. Profound understanding and thorough knowledge of both normal and abnormal anatomy considered as a critical factor in determining the success of endodontic therapy. The endodontic treatment of multi-rooted teeth was always a challenging task for dental practitioners. Therefore, a successful endodontic therapy should be always combined by a thorough knowledge as well as the use of specialized and innovated techniques for diagnosis, debridement and obturation. The current review article attempts to list out all the variations of permanent mandibular first molar root canal number in more than thirty studies and case reports published so far.